Pengaruh Penyuluhan 1000 Hari Pertama Kehidupan (HPK) pada Pasangan Usia Subur di Perkotaan dan Perdesaan - Agus Hendra Al Rahmad (Jurnal Kesehatan, 2019)
Nutrition improvements in the group of the first 1000 days of life will support the growth process from pregnancy to children aged 2 years. The main factor of nutrition improvement is knowledge about the first 1000 days of life. Nutritional adequacy in the first 1000 days of life affects the lives of infants and children aged 2 years, Aceh province shows 23,7% of Aceh children suffer from malnutrition. Then to increase knowledge, conducted counseling about the first 1000 days of life. The goal is to compare the effectiveness of counseling to increase knowledge of couples of childbearing age in urban and rural areas. Quantitative research designed quasi-experiment. Samples are 100 couples people. The location of the research was conducted in Baiturrahman and Darul Kamal Subdistricts, research was conducted on 26-28 July 2017. Data collection includes primary and secondary data, Then processed through the stages of editing, coding, processing, and cleaning. Data analysis using T-Test. The Results, there is an increasing influence of counseling the first 1000 days of life to couples of childbearing age in urban and rural areas, with p<0,05. Counseling the first 1000 days of life to have better effectiveness in improving knowledge couples of childbearing age, with p<0,05. While the comparison of knowledge, the average score in urban (50) is higher compared with rural (45). Conclusion, counseling the first 1000 days of life take effect to Increased knowledge of couples of childbearing age and have better effectiveness, as well as a higher knowledge increase in urban areas than in rural areas.